Diffusion Tensor Tractography Studies of Central Post-stroke Pain Due to the Spinothalamic Tract Injury: A Mini-Review - Jang, Sung Ho; Seo, Jeong Pyo; Lee, Sung Jun (Frontiers in Neurology, 2019)
Elucidation of the pathophysiological mechanism of central post-stroke pain (CPSP) is essential to the development of effective therapeutic modalities for CPSP. However, the pathophysiological mechanism of CPSP has not yet been clearly elucidated. The recent development of diffusion tensor tractography (DTT) derived from diffusion tensor imaging (DTI) has allowed visualization and estimation the spinothalamic tract (STT), which has been considered the most plausible neural tract responsible for pathogenesis of CPSP. In this mini-review, six DTT studies in which CPSP due to STT injury in stroke patients was demonstrated are reviewed. The information provided in the reviewed studies suggests that DTT is useful to elucidation of the pathophysiological mechanism associated with CPSP. We believe that the reviewed studies will facilitate neurorehabilitation of stroke patients with CPSP. However, DTT studies of CPSP are still in the beginning stage because the total number (six studies) of the reviewed studies is very short and half were case reports. Therefore, further studies involving large numbers of subjects are warranted.